2013
DOI: 10.3389/fpls.2013.00225
|View full text |Cite
|
Sign up to set email alerts
|

P-proteins in Arabidopsis are heteromeric structures involved in rapid sieve tube sealing

Abstract: Structural phloem proteins (P-proteins) are characteristic components of the sieve elements in all dicotyledonous and many monocotyledonous angiosperms. Tobacco P-proteins were recently confirmed to be encoded by the widespread sieve element occlusion (SEO) gene family, and tobacco SEO proteins were shown to be directly involved in sieve tube sealing thus preventing the loss of photosynthate. Analysis of the two Arabidopsis SEO proteins (AtSEOa and AtSEOb) indicated that the corresponding P-protein subunits do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 37 publications
4
32
0
Order By: Relevance
“…Therefore we searched for A. thaliana mRNAs that had one or more plausible miRNA complementary sites and accumulation of secondary siRNAs specifically in the I small RNA-seq samples. Six A. thaliana mRNAs that met both criteria were found: TIR1 , AFB2 , and AFB3 , which encode related and partially redundant auxin receptors 15 , BIK1 , which encodes a plasma membrane-localized kinase required for both pathogen-induced and developmental signaling 16,17 , SEOR1 , which encodes a major phloem protein that accumulates in filamentous networks in sieve tube elements and reduces photosynthate loss from the phloem upon injury 18,19 , and SCZ/HSFB4 , which encodes a predicted transcriptional repressor that is required for the formation of ground tissue stem cells in roots 20 - 22 . The induced siRNAs from these mRNAs resembled other examples of secondary siRNAs in their size distributions, double-stranded accumulation, and phasing (Figure 2A-B; Extended Data Figure 2).…”
mentioning
confidence: 99%
“…Therefore we searched for A. thaliana mRNAs that had one or more plausible miRNA complementary sites and accumulation of secondary siRNAs specifically in the I small RNA-seq samples. Six A. thaliana mRNAs that met both criteria were found: TIR1 , AFB2 , and AFB3 , which encode related and partially redundant auxin receptors 15 , BIK1 , which encodes a plasma membrane-localized kinase required for both pathogen-induced and developmental signaling 16,17 , SEOR1 , which encodes a major phloem protein that accumulates in filamentous networks in sieve tube elements and reduces photosynthate loss from the phloem upon injury 18,19 , and SCZ/HSFB4 , which encodes a predicted transcriptional repressor that is required for the formation of ground tissue stem cells in roots 20 - 22 . The induced siRNAs from these mRNAs resembled other examples of secondary siRNAs in their size distributions, double-stranded accumulation, and phasing (Figure 2A-B; Extended Data Figure 2).…”
mentioning
confidence: 99%
“…A fusion between the splitmRFP variants to the monomeric Emerald protein (mEmerald) was used as a control. [7][8][9][11][12][13] All BIFC constructs were introduced into Agrobacterium tumefaciens strain GV3101 pMP90 by electroporation and the resulting bacteria were infiltrated into 4-wk-old N. benthamiana plants. A. tumefaciens strain C58C1 (carrying the pCH32 helper plasmid) was co-infiltrated to inhibit gene silencing.…”
Section: Methodsmentioning
confidence: 99%
“…32 The Fluorescent experimental studies have shown that plugging complexes in wounded transgenic plants formed distinctive plugs on most sieve plates, and these plugs ends up with characteristic gel-like transcellular strands, consistent with the known characteristics of P-proteins. 33,34 P-proteins have been identified in many dicot plants, and their structural and functional role during developmental phase and sieve plate plugging after wounding appear highly conserved even in distantly related species.…”
Section: 12mentioning
confidence: 99%
“…15 Wide range of studies have been conducted on Medicago truncatula and Glycine max (GmSEO-F1-F4) regarding SEO-F protein to gain further insight characterizing gene encoding as forisomettes (forisome subunit), which assemble into a special type of crystalloid P-protein unique in Fabaceae. 34 Studies based on heterologous expression it is known that either MtSEO-F1 or MtSEO-F4 expressed individually can assemble into a homomeric protein complex which is similar to the native forisomes with respect to its structure and function. 45 This homomeric protein assembly has a spindle shaped body and longitudinally arranged fibrils and due to its similarity with the native forisomes is often described as the artificial forisomes.…”
mentioning
confidence: 99%